General decay for a von Karman equation with memory and time-varying delay. (December 2021) - Kang, Jum-Ran
Abstract: This paper is concerned with a von Karman equation with memory and time-varying delay. For a more general type of relaxation function β, we prove the general decay results. This work generalizes and improves previous results for the von Karman equation.